Flammability properties of polypropylene containing montmorillonite and some of silicon compounds - A.A. Younis (Egyptian Journal of Petroleum)
New polypropylene (PP) blends were prepared using phenyltrimethoxysilane (PTMS), glycidoxypropyltrimethoxysilane (GPTMS) and potassium-montmorillonite (K-MMT). Polymers A (K-MMT/PTMS), B (MMT/GPTMS) and C (modified-MMT) were prepared using sol-gel technique then incorporated in the PP matrix by different concentrations. Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimeter (DSC) were used to investigate the structure and thermal stability. The mechanical properties (tensile strength/TS and elongation/%) were measured. The flame-retardant properties of the unblended and blended (PP/A, PP/B and PP/C) were estimated by limiting oxygen index (LOI), flame chamber (UL/94) and oxygen bomb calorimeter (OBC) tests, whereas the thermal stabilities were investigated using TGA were carried flammability out to detect the properties of the blended PP.